Impact of learning conditions on young FL learners' motivation - Mihaljević Djigunović, Jelena (Array, 2007)
This paper describes a study investigating motivation of 100 Croatian early EFL beginners who started their FL learning in Grade 1 of primary school (age: 6-7) as part of their compulsory curriculum. In contrast to the 1991-2001 Croatian early FL learning project (Vilke 1993, 1995), participants in this study were taught under non-experimental conditions: they were not split into groups for their EFL classes, were taught by EFL teachers who were not specifically trained to work with YLs, and had fewer language classes per week (3 vs. 5). YLs' motivation was measured by a semi-structured interview which probed into learners' attitudes to English, to class activities and to NSs, wish to learn EFL, and parental attitudes. The results were compared with those obtained in the earlier studies cited above (Mihaljevic Djigunovic 1993, 1995), and interpreted against the changed socio-educational conditions of learning. This new study on young EFL learners' motivation offers insights that highlight the significance of the learning context for YLs' motivation.